The Cross-Sectional Association Between Multimorbidity and Sleep Quality and Duration Among the Elderly Community Dwellers in Northwest China - Nuermaimaiti Q; Heizhati M; Luo Q; Li N; Gan L; Yao L; Yang W; Li M; Li X; Aierken X; Hong J; Wang H; et al. (Nature and Science of Sleep)
Qiaolifanayi Nuermaimaiti,1– 6,* Mulalibieke Heizhati,1– 6,* Qin Luo,1– 6 Nanfang Li,1– 6 Lin Gan,1– 6 Ling Yao,1– 6 Wenbo Yang,1– 6 Mei Li,1– 6 Xiufang Li,1– 6 Xiayire Aierken,1– 6 Jing Hong,1– 6 Hui Wang,1– 6 Miaomiao Liu,1– 6 Adalaiti Maitituersun,1– 6 Aketilieke Nusufujiang,1– 6 Li Cai1– 6 1Hypertension Center of People’s Hospital of Xinjiang Uygur Autonomous Region, Urumqi, Xinjiang, 830001, People’s Republic of China; 2Xinjiang Hypertension Institute, Urumqi, Xinjiang, 830001, People’s Republic of China; 3NHC Key Laboratory of Hypertension Clinical Research, Urumqi, Xinjiang, 830001, People’s Republic of China; 4Key Laboratory of Xinjiang Uygur Autonomous Region, Urumqi, Xinjiang, 830001, People’s Republic of China; 5Hypertension Research Laboratory, Urumqi, Xinjiang, 830001, People’s Republic of China; 6Xinjiang Clinical Medical Research Center for Hypertension (Cardio-Cerebrovascular) Diseases, Urumqi, Xinjiang, 830001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qin Luo; Nanfang Li, Hypertension Center of People’s Hospital of Xinjiang Uygur Autonomous Region, No. 91 Tianchi Road, Urumqi, Xinjiang, 830001, People’s Republic of China, Tel/Fax +86 0991 8564816, Email luoqin2@sina.cn; lnanfang2016@sina.comBackground: Multimorbidity, defined as the coexistence of two or more chronic diseases, is highly prevalent among the elderly population and is associated with adverse outcomes. However, little is known about its relationship with sleep issues, particularly in this demographic. Therefore, this study aimed to investigate its association with sleep quality and duration among the elderly.Methods: This cross-sectional study was conducted in Emin County, Xinjiang, China, which included a population aged 60 years and above. We employed the Pittsburgh Sleep Quality Index (PSQI) score to assess sleep quality and duration. Multimorbidity was determined through self-reports, physical examination, blood tests, and imaging. Logistic regression analyses were used to explore the association between multimorbidity and sleep patterns, adjusting for confounders.Results: A total of 8205 elderly participants were included, of whom 66.8% suffered from multimorbidity. Participants with multimorbidity exhibited higher total PSQI scores [6 (3,9)], and a higher percentage of poor sleep quality (50.6%), compared to those without multimorbidity. Multimorbidity was significantly associated with the presence of poor sleep quality (OR = 1.27, 95% CI: 1.14– 1.41, P < 0.001) before and after adjusting for confounders. The risk of having poor sleep quality significantly increased as the number of multimorbidities increased. The OR (95% CI) values were 1.16 (1.02,1.32) for two diseases, 1.54 (1.26,1.90) for ≥ 5 diseases. In the adjusted model for total participants, having four diseases (OR = 1.26, 95% CI: 1.05– 1.51, p = 0.013) and five or more diseases (OR = 1.29, 95% CI: 1.03– 1.61, p = 0.029) were associated with shorter sleep duration. Furthermore, those with five or more diseases associated with longer sleep duration (OR = 1.40, 95% CI: 1.00– 1.95, p = 0.057).Conclusion: There is a significant association between multimorbidity and poor sleep quality in older community dwellers, which may provide clues for disease prevention.Keywords: multimorbidity, sleep quality, sleep duration, elderly